A short course of corticosteroids reduces the risk of mechanical ventilation and death in patients with moderate to severe COVID 19 pneumonia: results of a retrospective monocentric cohort. Issue 10 (3rd October 2021) - Comparon, Celine; Boubaya, Marouane; Sritharan, Nanthara; Dournon, Nathalie; Duchemann, Boris; Tine, Samir; Lopez-Sublet, Marilucy; Mongin, Marie; Giroux-Leprieur, Bénédicte; Bloch-Queyrat, Coralie; Sigaux, Johanna; Cohen, Yves; et al.
Abstract: Background: Reduced mortality at 28 days in patients treated with corticosteroids was demonstrated, but this result was not confirmed by certain large epidemiological studies. Our aim was to determine whether corticosteroids improve the outcomes of our patients hospitalized with COVID-19 pneumonia. Methods: Our retrospective, single centre cohort study included consecutive patients hospitalized for moderate to severe COVID-19 pneumonia between March 15 and April 15 2020. An early short course of corticosteroids was given during the second phase of the study. The primary composite endpoint was the need for mechanical ventilation or mortality within 28 days of admission. A multivariate logistic regression model was used to estimate the propensity score, i.e. the probability of each patient receiving corticosteroid therapy based on the initial variables. Results: About 120 consecutive patients were included, 39 in the "corticosteroids group", 81 in the "no corticosteroids group"; their mean ages (±SD) were 66.4 ± 14.1 and 66.1 ± 15.2 years, respectively. Mechanical ventilation-free survival at 28 days was higher in the "corticosteroids group" than in the "no corticosteroids group" (71% and 29% of cases, respectively, p  < .0001). The effect of corticosteroids was confirmed with HR .28 (95%CI .10–.79), p  = .02. In older and comorbid patients who were not eligible for intensive care, the effect of corticosteroid therapy was also beneficial (HR .36 (95%CI .16–.80), p  = .01). Conclusion: A short course of corticosteroids reduced the risks of death or mechanical ventilation in patients with moderate to severe COVID-19 pneumonia in all patients and also in older and comorbid patients not eligible for intensive care.